NOSTALGIA, EXPULSION AND THE POETIC I: THE POETICS OF DIASPORA IN THE CORPUS THEOGNIDEUM - Skarbek-Kazanecki, J (Akroterion, 2022)
In the anthology of archaic elegiac poetry called the Corpus Theognideum, the poetic I often eludes traditional approaches to the ‘poetic authority’. Instead of presenting itself as a citizen of a particular ‘city-state’ or at least a prominent member of an elitist circle who came to have a position of authority, the persona loquens situates himself as removed from the community: as impoverished, expelled from his polis, despised, embittered and thirsting for revenge. The purpose of my paper is to consider how the tension between the alienation of the poetic I and the unity of the audience might function during the act of (re)performance. Applying considerations of Edward W Said on ‘diasporic temporality’ to the political and economic conflict between the ideologies of polis and anti-polis in archaic and classical Greece, I show that the poetic I in the Theognidean tradition, by presenting itself as an exile and a victim of the democratic movement, expresses the temporally distant position of the so far privileged aristocracy, situated in dialectical opposition to the democratic institutions of polis.